2010
DOI: 10.3109/09638281003797331
|View full text |Cite
|
Sign up to set email alerts
|

‘This constant being woken up is the worst thing’ – experiences of sleep in fibromyalgia syndrome

Abstract: Theadom A, Cropley M (2010). 'This constant being woken up is the worst thing' -experiences of sleep in fibromyalgia syndrome. Disability and Rehabilitation 32(23):1939-1947 'This constant being woken up is the worst thing' -experiences of sleep in fibromyalgia syndrome Alice Theadom and Mark Cropley Abstract Purpose. Sleep disturbance affects a high proportion of people with fibromyalgia syndrome (FMS). This study aims to explore people's perceptions of their sleep quality and the influence sleep has on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 45 publications
7
30
0
1
Order By: Relevance
“…We found that almost all of the patients in the present study perceived increased pain to lead to poorer sleep, corroborating the impact of pain on sleep in previous qualitative and quantitative studies (Smith et al, 2000; Breivik et al, 2006; Hawker et al, 2008; Ashworth et al, 2010; Theadom and Cropley, 2010; Henderson et al, 2013; Thomazeau et al, 2014). For example, many chronic pain patients firmly believe that when they are in pain, it is simply impossible for them to get comfortable and go to sleep (Edwards et al, 2011; Tang et al, 2012a).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that almost all of the patients in the present study perceived increased pain to lead to poorer sleep, corroborating the impact of pain on sleep in previous qualitative and quantitative studies (Smith et al, 2000; Breivik et al, 2006; Hawker et al, 2008; Ashworth et al, 2010; Theadom and Cropley, 2010; Henderson et al, 2013; Thomazeau et al, 2014). For example, many chronic pain patients firmly believe that when they are in pain, it is simply impossible for them to get comfortable and go to sleep (Edwards et al, 2011; Tang et al, 2012a).…”
Section: Discussionsupporting
confidence: 91%
“…The experience and expression of such pain is commonly modulated by the presence of comorbid conditions like sleep and mood disturbances (Chiu et al, 2005; Lautenbacher et al, 2006; Roehrs et al, 2006; Haack et al, 2007; Smith et al, 2007; O’Brien et al, 2011; Blagestad et al, 2012) as well as expectancies and appraisals about these conditions (Tracey, 2010; Bjorkedal and Flaten, 2012). Chronic pain patients often attribute specific causal relationships in terms of how these conditions influence each other (Morin et al, 1998; Hawker et al, 2008; Tang et al, 2009; Theadom and Cropley, 2010). Shown to shape symptom expression, such attributions also influence a person’s overall perceived symptom load (Petrie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disrupted sleep cycles, reported as one of the most bothersome FM-related symptoms [18][19][20][21], cause individuals to wake up feeling unrefreshed [22] and have been correlated with increases in perceived severity of FM-related pain, fatigue, and depressed mood [22][23][24][25][26][27][28]. A 2014 study [29] found that the strongest predictor of new onset widespread pain in older adults was non-restorative sleep but that a return to a restorative sleep pattern resulted in resolution of the widespread pain.…”
Section: Introductionmentioning
confidence: 99%